Consumos lectores entre adolescentes: Un abordaje comparado desde contextos internacionales. El caso de Polonia, Chile y Portugal - Carolina Margarita González Ramírez; Marek Baran; Pedro Dono López; Inmaculada Carbonell Sánchez (Investigaciones Sobre Lectura)
This contribution evaluated aspects, such as the frequency of reading, formats, and reading preferences, of secondary school students from Poland, Chile, and Portugal. For this, we started with the data obtained from a questionnaire on reading interests and frequencies, answered by 491 schoolchildren from the referred countries (175 Poles, 178 Chileans, and 138 Portuguese), on which a contrastive analysis was carried out with the aim of observing whether the strategies for promoting and consolidating reading habits should follow similar or divergent guidelines in each of the contexts. The comparison of the results indicates low reading frequencies are common to all the countries of the study, highlighting the lack of interest in reading periodicals (newspapers and magazines) and comics, although in leisure time (particularly on holidays) respondents show a greater interest in reading. Their preferences are oriented toward the adventure genre, which is followed by books on romantic themes, science fiction, mystery, terror, and humor. As for specific works and authors, we found a very heterogeneous and diverse panorama for each country. They show, in general terms, a penchant for paper in relation to reading support (e-books, in particular, are not particularly appreciated); however, a large contingent of schoolchildren are indifferent to the format. Digital reading is largely dominant in social networks. The analysis of the results reveals an important confluence in the three contexts analyzed, pointing in general to a low frequency and motivation toward reading, which is why common strategies are proposed to enhance the reading habits of Polish, Chilean, and Portuguese schoolchildren.